A-DO. 1 - Jaku, Amano (Kodansha USA Publishing, LLC, 2024)
"Following a wave of immigration, Japan has became a volatile mix of people and cultures, rocked by the protests of xenophobic extremists unhappy with the new status quo. A brash, job-hopping young woman named Riko is driving her scooter through one such protest when she sees a boy about to get run over by a truck. Riko just manages to shove him out of the way, and, in the hours that follow, she finds herself looking after the boy, named Eito. Riko takes Eito out for a bowl of ramen, but just as they're about to dig in, Eito is fired upon by a distant army sniper. As the bullet pierces the restaurant window and comes whizzing toward Eito, plant-like tendrils snake out from his arm and stop it in mid-flight. Who in the world is this boy, and why is the army after him?!"--